Features of piezoresistance in heavily doped n-silicon crystals - Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
It has been shown that in silicon single crystals heavily doped with arsenic the presence of the temperature gradient at the interface of the liquid and solid phases in the process of growing them from a melt does not lead to anisotropy of piezoresistance under the passing current both along the direction of deforming load (J || X || 111) and perpendicularly to it (J ⊥ X || 111). This is considered as an evidence of the dominant influence of randomization in spatial distribution of a dopant due to kT (at T = 1685 K) during the growth of single crystals.